Effekten av människans omvårdnadsstil på hundars reaktion på en främmande person - Schultzén, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
The dog (Canis familiaris) has been a part of human lives for so long that they are considered as family members by many people. They probably attach themselves to us in different ways depending on what nursing style humans use. This study included two different nursing styles, secure (S) and unpredictable (U), applied on 11 dogs over an interaction period of 15 days. The test involved a dog with its handler (S or U) sitting in a room, then a stranger entered the room and walked a specific route before exiting. Dogs were tested two times, each dog subjected to the two different nursing styles. Recorded videotapes of the tests were observed during three minutes (before, during and after stranger presence) in five second intervals. For the entire test the dogs were wearing heart rate (HR) monitors. Results show that the dogs walked/ran more with an unpredictable handler in the room while the stranger was present (P = 0,042). There were tendencies for the dogs to orient towards the door more in company with the U handler before the stranger entered and orient towards the U handler more when the stranger was in the room. The dogs had a higher HR while being with the U handler, during the 30-59 seconds after stranger presence (P = 0,046). These results can be interpreted as the dogs being more uncomfortable and becoming more nervous around the U handler. Hence, a secure nursing style may help to get a calm, safe dog and a sustainable relationship. The dogs in this study were tested only a short while and did not have enough time to attach themselves to the handlers and thus no safe base could be seen. Also, no results were found for the dogs’ interest to follow the stranger out when exiting the room. This study can be used for future research within human-animal interactions in order to enhance dogs’ welfare.